Analisis Strategi Pengelola dalam Meningkatkan Partisipasi Warga Belajar untuk Mengikuti Kegiatan belajar di Sikkola Rakyat - Sani Susanti; Maya Anggelina; Nazwa Azzahra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the management strategy of Sikkola Rakyat to increase student engagement in learning. Important issues related to student participation in Sikkola Rakyat are discussed, and an innovative model for an inclusive participatory management system is proposed. It is hoped that this model can make a major contribution to improving the quality of education by empowering students, strengthening community collaboration, and creating a more effective and sustainable learning atmosphere. The approach used in this study is qualitative with the Miles and Huberman model. Data collection techniques include observation and interviews. Observations were carried out directly at Sikkola Rakyat to see how education management takes place. Interviews were conducted with the Head of Education Division at Sikkola Rakyat and the Partnership Manager at Sikkola Rakyat Pusat at the Jalur Hijau learning house. The research findings indicate that Sikkola Rakyat implements student-focused learning strategies, including interactive methods, ice breaking, and giving small awards to motivate children. The decision-making process is internal but remains open to feedback from the community. Teaching methods are adjusted to the age of the child, and teaching materials are adapted according to the abilities of the students. Volunteers are trained through regular micro teaching as well as social observation and analysis stages. Although the facilities are limited, the learning atmosphere remains fun by using games, quizzes, prizes, and casual discussions. There are positive changes in children after they join Sikkola Rakyat, such as the implementation of the